1998
DOI: 10.1074/jbc.273.21.13015
|View full text |Cite
|
Sign up to set email alerts
|

The Human Poly(A)-binding Protein 1 Shuttles between the Nucleus and the Cytoplasm

Abstract: We have studied the intracellular localization of poly(A)-binding protein 1 (PABP1) by indirect immunofluorescence as well as by tagging with the green fluorescent protein (GFP) in living cells. We show that PABP1 is able to enter the nucleus. Accumulation of PABP1 in the nuclei was observed upon transcription inhibition, suggesting that active transcription is required for PABP1 export. The nuclear import of PABP1 is an energy-dependent process since PABP1 fails to enter the nucleus upon ATP depletion and at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
163
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(172 citation statements)
references
References 51 publications
8
163
0
1
Order By: Relevance
“…Early work suggested that the C terminus is important in structuring the mRNA tail and for the cellular localization of PABP. This work was confirmed by more recent studies that describe PABP dimerization through the C-terminal domain and a requirement of the C terminus for proper nuclear shuttling (11,12). The C-terminal half of PABP contains binding sites for eRF3 (5), Paip1 (13), Paip2 (4), Pbp1p (7), and a viral RNA polymerase (14).…”
Section: P Oly(a)-binding Protein (Pabp) Is a Ubiquitous And Abundantsupporting
confidence: 69%
“…Early work suggested that the C terminus is important in structuring the mRNA tail and for the cellular localization of PABP. This work was confirmed by more recent studies that describe PABP dimerization through the C-terminal domain and a requirement of the C terminus for proper nuclear shuttling (11,12). The C-terminal half of PABP contains binding sites for eRF3 (5), Paip1 (13), Paip2 (4), Pbp1p (7), and a viral RNA polymerase (14).…”
Section: P Oly(a)-binding Protein (Pabp) Is a Ubiquitous And Abundantsupporting
confidence: 69%
“…Alternatively, the presence of pUL69 in the complex could make 4EBP1 more susceptible to phosphorylation, which would then cause its exclusion. Although primarily cytoplasmic proteins, a portion of 4EBP1 (30), eIF4E (31), PABPC1 (32,33), and pUL69 (16) are present in the nucleus, so it is possible that pUL69 prevents association of 4EBP1 with cap-associated proteins in the nucleus, even before the mRNA is transported to the cytoplasm. An interaction of pUL69 with nuclear RNAs through PABPC1 could also contribute to its role in mRNA nucleocytoplasmic transport (12).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of mammalian and yeast pre-mRNA 39-end-processing components reveals that, although many homologies can be found, the proteins are not function-ally interchangeable (for a recent review, see )+ An apparent case of divergence during evolution occurs with poly(A)-binding proteins+ Yeast contains a single poly(A)-binding protein (termed Pab1p), which is an essential protein present in both the nucleus and the cytoplasm (Sachs et al+, 1986)+ In the nucleus it stimulates polyadenylation and controls poly(A) tail length (Amrani et al+, 1997;MinvielleSebastia et al+, 1997;Brown & Sachs, 1998), whereas in the cytoplasm it is involved in translation initiation (Sachs & Davis, 1989;Sachs & Deardorff, 1992;Tarun & Sachs, 1995, 1996Le et al+, 1997) and mRNA degradation (Caponigro & Parker, 1995;Boeck et al+, 1998;Coller et al+, 1998)+ In contrast, mammalian cells contain two distinct proteins called poly(A)-binding protein I (PABP1) and poly(A)-binding protein II (PAB II or PABP2)+ PABP1 is predominantly detected in the cytoplasm (Görlach et al+, 1994), whereas PABP2 is localized in the nucleus (Wahle, 1991;Krause et al+, 1994)+ PABP1, which is the mammalian counterpart of yeast Pab1p (51% identity), is apparently involved in both cytoplasmic mRNA stability (Bernstein et al+, 1989;Wormington et al+, 1996;Afonina et al+, 1997;Ford et al+, 1997;Körner & Wahle, 1997) and translation (Craig et al+, 1998), but to date there is no evidence that it participates in nuclear pre-mRNA 39-end processing (see )+ Consistent with its nuclear localization, PABP2 is the mammalian protein involved in polyadenylation+ PABP2 stimulates processive poly(A) addition and controls the size of the tail to be ;250 nt in length (Wahle, 1991(Wahle, , 1995Bienroth et al+, 1993)+ How PABP2 bound to poly(A) tails in the nucleus is replaced by PABP1 in the cytoplasm remains unknown, but recent evidence indicates that both PABP1 and PABP2 shuttle between nucleus and cytoplasm (Afonina et al+, 1998;Chen et al+, 1999)+ Because it is not known when PABP1 exchanges with PABP2, one possibility is that PABP2 crosses the nuclear pores in association with the mRNA and dissoci...…”
Section: Introductionmentioning
confidence: 99%